2019
DOI: 10.1007/s40596-019-01047-5
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Childhood Experiences in Medical Students: Implications for Wellness

Abstract: Objective The primary purpose of the study was to assess the prevalence of adverse childhood experiences (ACEs) in a cohort of third-year medical students and characterize their childhood protective factors. Methods The authors developed a web-based anonymous survey distributed to all third-year medical students in one school ( N = 98). The survey included the 10-item ACE Study questionnaire, a list of childhood protective factors (CPF) and qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 31 publications
(27 reference statements)
4
38
0
Order By: Relevance
“…MSM in our study reported higher scores of ACE, with over half of participants reporting one or more ACE exposures, compared to general male population [13, 49]. Our results showed a strong positive association of ACE with depressive symptoms, which was in accordance with that of previous studies [1315].…”
Section: Discussionsupporting
confidence: 92%
“…MSM in our study reported higher scores of ACE, with over half of participants reporting one or more ACE exposures, compared to general male population [13, 49]. Our results showed a strong positive association of ACE with depressive symptoms, which was in accordance with that of previous studies [1315].…”
Section: Discussionsupporting
confidence: 92%
“…Students may use the AMCAS disadvantaged (SDA) prompt to disclose their experiences in a marginalized or underrepresented group, which may not otherwise be included in their application. Reporting SDA+ may reflect exposure to childhood adverse experiences, 33 including childhood maltreatment, bullying, and growing up with mental illness or substance use 34 in the family. 35,36 Students from negatively stereotyped or devalued social groups are more likely to experience bias and discrimination, 37,38 low self-efficacy and sense of belonging, 34,39,40 imposter syndrome (i.e., the feeling that they do not deserve to "be there" and that they have simply fooled anyone who thinks otherwise) 41 and microaggressions 42 -any one of which may adversely affect academic progression in medical school.…”
Section: Discussionmentioning
confidence: 99%
“…Two papers in this collection take very different approaches to exploring the etiology of burnout and depression during psychiatry training. Sciolla et al [5] attempt to place these issues in the context of developmental trauma and adverse childhood experiences (ACEs) of medical students. Although robust evidence shows that ACEs are a strong risk factor for later depression, suicidality, and substance abuse [6], there is a paucity of data on medical student populations.…”
Section: Understanding the Problem And Its Originsmentioning
confidence: 99%
“…Most of the cohort reported that they compared themselves to their peers to a moderate or great degree, and close to half reported that their self-worth was tied to their performance relative to their classmates. It is important to recognize, however, that both the Sciolla et al [5] and Hu et al [8] studies are limited by methodological challenges, including relatively small samples and a potential lack of generalizability of results.…”
Section: Understanding the Problem And Its Originsmentioning
confidence: 99%